A case study on rainfall dynamics during El Niño/La Niña 1997/99 in Ecuador and surrounding areas as inferred from GOES-8 and TRMM-PR observations - Bendix, Jörg; Gämmerler, Stefan; Reudenbach, Christoph (ERDKUNDE, 2003)
El Niño and La Niña (EN/LN) events cause heavy precipitation, floods and various economical losses in the normally extreme dry coastal areas of southern Ecuador and northern Peru (El Niño) as well as at the eastern-Andean slopes (La Niña), respectively. Due to the fact that the spatio-temporal rainfall distribution and rainfall formation during super events is still not definitely known today, an analysis of heavy precipitation dynamics during the strongest Super El Niño of the last century (1997/98) for Ecuador and northern Peru and the following La Niña (1999) event is presented. The investigation is based on half-hourly time series of GOES-8 and additional radar data onboard the TRMM platform (PR-Sensor). The Enhanced Convective Stratiform Technique (ECST) was applied to compute precipitation maps in order to examine the spatio-temporal rainfall distribution. Additionally, Cloud Motion Winds (CMW) are extracted from the GOES-8 data in order to investigate the related circulation pattern. It has been proven that the spatio-temporal dynamics of heavy precipitation during the Super El Niño 1997/98 reveals the same mechanisms as during a normal El Niño (1991/92). However, the rainfall amount is significantly increased. Evidence for clear spill-over effects of cirrus remainders from the Amazon region on the rainfall formation in the coastal lowlands could be found by means of TRMM-PR data and CMW's. The La Niña situation (1999) is typified by an inverse spatial distribution of rainfields. The specific La Niña weather situation with its typical circulation patterns is outlined.